If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + 6 = 8 + 8p Reorder the terms: 6 + 9p = 8 + 8p Solving 6 + 9p = 8 + 8p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-8p' to each side of the equation. 6 + 9p + -8p = 8 + 8p + -8p Combine like terms: 9p + -8p = 1p 6 + 1p = 8 + 8p + -8p Combine like terms: 8p + -8p = 0 6 + 1p = 8 + 0 6 + 1p = 8 Add '-6' to each side of the equation. 6 + -6 + 1p = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 1p = 8 + -6 1p = 8 + -6 Combine like terms: 8 + -6 = 2 1p = 2 Divide each side by '1'. p = 2 Simplifying p = 2
| 9(13-x)-4x=5(21-2x)9x | | -6x-4y=12 | | 3(5x+9)=-78 | | 6(-3-3x)=-72 | | 3x^2+4=5x | | 2+2=k | | 5(1x-4)=-5 | | ln(y-4)-ln(5)=5x+ln(x) | | 8.2x-2.3x=-177 | | -1-2x=-7x-41 | | 20-(-4k)=32 | | -6+6x=-4x+94 | | (3)(2)-(2)(3)+(2)(3)= | | -4+x=-2x-10 | | 15-1(4k-5)=32 | | 9(y+9)+y=3(y+2)+4 | | 2x^2+19x=-174 | | b+b+b+7=b+22 | | 8x=3(x+5) | | h(t)=-16t^2+34t | | 3x-2y+xy= | | -1t^2+1t+3=0 | | -5=z+3 | | -1X^2+1X+3=0 | | -7/8=-w/4 | | -7/8=w/4 | | 4m+10=70 | | 8x+1=49 | | 26p+41l=210 | | 25=42 | | 3s-13=-27+s | | 41L+26p=210 |